IMPACT OF MATERNAL NUTRITIONAL STATUS DURING PREGNANCY ON STUNTING RISK AMONG CHILDREN AGED 24-59 MONTHS (The Research of Medical Science Review, 2025)
Background: Stunting remains a major public health challenge, particularly in low- and middle-income countries. Maternal nutritional status during pregnancy is a key determinant of child growth and development, yet its impact on stunting risk among children aged 24–59 months is underexplored. Objective: This study aimed to investigate the association between maternal nutritional status during pregnancy and the risk of stunting among children aged 24–59 months. Methods: This retrospective observational study was conducted at the Pediatrics Department and Gynecology & Obs Department of Khyber Teaching Hospital and Obs & Gynae Deptt.of Hayatabad Medical Complex Peshawar from January 2020 to December 2024. A total of 150 mother-child pairs were enrolled, with data collected on maternal nutrition, birth outcomes, and child growth at 24–59 months. Stunting was defined as height-for-age z-score (HAZ) <-2 SD. Multivariate logistic regression was used to identify predictors of stunting. Results: The prevalence of stunting was 24% (n=36). Maternal undernutrition (aOR=2.8, p<0.001), low birth weight (aOR=2.5, p<0.01), inadequate dietary diversity (aOR=1.8, p=0.02), and household food insecurity (aOR=1.6, p=0.04) were significant predictors of stunting. Conclusion: Maternal nutritional status during pregnancy plays a criticaln role in determining stunting risk. Interventions targeting maternal nutrition, infant feeding practices, and household food security are essential to reduce stunting and improve child health outcomes.